PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 15 LUBUK MUDA KECAMATAN SIAK KECIL KABUPATEN BENGKALIS - Yunita, Herma; Antosa, Zariul; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research carried out base on the lowly of the result of IPS in grade 4th SDN 15 Lubuk Muda Kecamatan Siak Kecil Kabupaten Bengkalis which is about 62,66 within minimal completeness criterion stated is 70. Among 15 student, there was only 4 students were able to achieve the score of minimal completeness criterion stated. The purpose of this research is to improve student’s achievemet on IPS of the fourth graders in SDn 15 Lubuk Muda Kecamatan Siak Kecil Kabupaten Bengkalis with the application of contextual teaching and learning model. This research was classroom action research consisting 2 cycles within 4 procedures : planning, doing, observing, and reflecting and each cycle consist of three meeting. Instruments on this research are syllabus, lesson plan, and student work sheet. Instrument for collecting data are observation sheet and test. Data which was collected were learning outcomes and teacher’s activities during lessons. After implementation of contextual teaching and learning model it was abtained student’s outcomes in UH I within average 64,66 (improved from basic score 3,19%). The average score form UH II was 73,66 (improved 17,55%). Teachers activities results in the first meeting of the first cycle was 57,14% (enough category), and then 67,85% (good category) for the second meeting in cycle I. Meanwhile in the first meeting of the second cycle was 78,57% (good category) and then 85,71% (very good category) for second meeting in cycle II. Students activity in the first meeting of the cycle I was 57,14% (fair category), 64,28% (enough category) for the second meeting in the cycle I. And then in the first meeting of the second cycle was 7,14% (good category), 78,57% (good category) for the second meeting in cycle II. Based on the result it can be concluded that implementation of contextual teaching and learning model can IPS in fourth graders at SDN 15 Lubuk Muda Kecamatan Siak Kecil Kabupaten Bengkalis.Keywords : Contextual Teaching and Learning, the result of IPS Studies.